1988
DOI: 10.1007/bf00972477
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptors in the brain: Structural and physiological characterization

Abstract: The present study was conducted to characterize insulin receptors and to determine the effects of insulin in synaptosomes prepared from adult rat brains. Binding of 125I-insulin to synaptosome insulin receptors was highly specific and time dependent: equilibrium binding was obtained within 60 minutes, and a t1/2 of dissociation of 26 minutes. Cross-linking of 125I-insulin to its receptor followed by SDS-PAGE demonstrated that the apparent molecular weight of the alpha subunit of the receptor was 122,000 compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…On the other hand, insulin is found to be able to increase the turnover rate of epinephrine and norepinephrine [214]. The effects of insulin on norepinephrine have been investigated in dissociated brain cells and synaptosomes prepared from the adult rat brain, and it is shown that norepinephrine uptake is inhibited by insulin [215,216]. Similar results are also reported in cell culture studies [217,218].…”
Section: Insulin and Neurotransmissionmentioning
confidence: 52%
“…On the other hand, insulin is found to be able to increase the turnover rate of epinephrine and norepinephrine [214]. The effects of insulin on norepinephrine have been investigated in dissociated brain cells and synaptosomes prepared from the adult rat brain, and it is shown that norepinephrine uptake is inhibited by insulin [215,216]. Similar results are also reported in cell culture studies [217,218].…”
Section: Insulin and Neurotransmissionmentioning
confidence: 52%
“…IR mRNA is abundantly present in neuronal somata (Schwartz et al, 1992). The neuronal IR binds insulin in a highly specific and rapid manner (Raizada et al, 1988). It has been hypothesized that the differing distribution patterns of insulin-1 and IRs in the brain may suggest that IRs in different brain regions may use insulin from different sources, either peripherally or locally synthesized, for cell-to-cell communication and neuronal signal transduction (Zhao et al 2004).…”
Section: Insulin Signaling In the Brainmentioning
confidence: 99%
“…Consistent with its enriched distribution in adrenergic terminals, insulin is found to promote central catecholaminergic activities by releasing both epinephrine and norepinephrine (20), inhibiting synaptic reuptake of norepinephrine (21), and altering catecholomine kinetics (22). In the hippocampus, insulin is reported to enhance ␣1 adrenergic receptor activity, leading to stimulation of membrane phosphoinositol turnover * The costs of publication of this article were defrayed in part by the payment of page charges.…”
mentioning
confidence: 91%